Unresolved abdominal mass - Shrestha, B; Baidya, JL (Kathmandu University Medical Journal, 2009)
A case of huge enhancing solid mass in the abdomen observed in 30 years old gentlemen is reported. Patient was worked up and managed conservatively outside valley with the provisional diagnosis of an appendicular lump. When examined, he was found to have huge intra abdominal mass. Interestingly when the genitalia was examined he was found to have underdeveloped empty scrotum without testes in it which he was yet not bothered. This simple examination gave us a straight clue to come up with the diagnosis of malignancy in undescended testes. Laparotomy was performed and the mass was excised. After 6 weeks postoperatively he was subjected for the chemotherapy. After 3 cycles of chemotherapy CT scan showed complete disappearance of retroperitoneal lymphadenopathy and serum tumor markers have come down to normal level. Key words: Germ cell tumor (GCT), Seminoma, Non seminomatous germ cell tumor, (NSGCT), Cryptorchidism, Alpha fetoprotein (AFP), Beta human chorionic gonadotrophin (BHCG), Lactate dehydrogenase (LDH) doi: 10.3126/kumj.v7i1.1773 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 82-85